2022
DOI: 10.3389/fmed.2022.827297
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy in Squamous Cell Carcinoma of the Esophagus and of the Head and Neck

Abstract: Squamous cell carcinomas of the esophagus (ESCC) and of the head and neck (HNSCC) are two neoplasms that share common risk factors and have the same embryological origin, but a very different prognosis, the 5-year survival of HNSCC being almost double (40–50%) compared to the 5-year survival of ESCC (20%). Current guidelines emphasize the importance of screening for ESCC in patients diagnosed with head and neck cancers. A liquid biopsy is a novel tool for diagnosis, prognostic stratification, and personalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…If PABPC1 expression is used as a biomarker to evaluate endoscopic patients, all PABPC1-HE patients should undergo further examination and treatment because the biomarker PPV was up to 100% (Monaghan et al , 2021). It is not noninvasive compared with liquid biopsy biomarkers in ESCC, such as exosome-related and serological miRNA markers (Iacob et al , 2022; Miyoshi et al , 2022). Thus, PABPC1 expression analysis should be more convenient since only immunohistochemistry is needed on endoscopic biopsy samples (Sukswai and Khoury, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…If PABPC1 expression is used as a biomarker to evaluate endoscopic patients, all PABPC1-HE patients should undergo further examination and treatment because the biomarker PPV was up to 100% (Monaghan et al , 2021). It is not noninvasive compared with liquid biopsy biomarkers in ESCC, such as exosome-related and serological miRNA markers (Iacob et al , 2022; Miyoshi et al , 2022). Thus, PABPC1 expression analysis should be more convenient since only immunohistochemistry is needed on endoscopic biopsy samples (Sukswai and Khoury, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…16 Further, the adaptability of TOFS technology facilitates its application in identifying patients likely to benefit from certain target immunotherapies, such as the detection of PD-1 and PD-L2 biomarkers to predict responsiveness to checkpoint inhibitor therapy. 17,18 In addition to the utility of TOFS in biomarker detection in the clinic, its application in liquid biopsy has the potential to bolster research in salivary biomarkers of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The cfDNA template is found in specific body fluids at very low concentrations, which may lead to the low sensitivity of detection. A growing body of evidence suggests that liquid biopsy has recently emerged as a new noninvasive technique of detecting blood circulating biomarkers for OSCC [116], e.g., detection of circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA) [117,118]. Authors have reported that a liquid biopsy is a novel tool for diagnosis, prognostic stratification, and personalized therapy, while liquid biopsy biomarkers for OSCC could be useful in early detection and may provide prognosis information [119].…”
Section: Znf582mentioning
confidence: 99%